Burden of General Surgical Cancer Care in West Africa: A Review of the Literature - Nikita Arora; Linda Fei; Matthew Jalink; Olusegun Isaac Alatise; Gregory Knapp; Faizal Haji; Emmanuel Ezeome; Sulaiman Nanji (JCO Global Oncology)
PURPOSEThe global burden of cancer is growing rapidly, with a disproportionately higher increase in low- and middle-income countries. West Africa is particularly affected by this rise, where cancer control systems are woefully inadequate to meet the increasing needs of patients. Although many gaps exist across the continuum of cancer care, perhaps the most striking is the lack of surgical services, which plays a vital role in up to 80% of all patients with cancer. To address this critical gap in cancer care, the West African College of Surgeons established a bilateral partnership with Queen's University, Canada, to grow the surgical oncology workforce for the region by cocreating and implementing a general surgical oncology fellowship training program.METHODSTo inform the design of the curriculum tailored to the cancer care needs of West Africa, a narrative review of the literature was performed to identify the incidence and mortality associated with general surgical cancers in the region, as well as the health care resources available to address these malignancies.RESULTSThis comprehensive report provides a contemporary understanding of the landscape of cancer care with respect to the burden of disease, the existing resources, and the challenges in delivery of cancer services for West Africa.CONCLUSIONThe findings in this report quantify the unmet demand for cancer care in West Africa and highlight the scope for context-specific cancer training in this region.